2013
DOI: 10.1007/s00011-013-0678-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angptl4 in vascular permeability and inflammation

Abstract: Taken together, Angptl4 modulates vascular permeability, angiogenesis, inflammatory signaling, and associated diseases. The use of Angptl4-modulating agents such as certain drugs, food constituents (such as fatty acids), nuclear factor (such as PPARα), and bacteria may treat associated diseases such as tumor metastasis, ischemic-reperfusion injury, inflammation, and chronic low-grade inflammation. However, the diverse physiological functions of Angptl4 in different tissues can lead to potentially deleterious s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 50 publications
2
80
0
Order By: Relevance
“…In the bloodstream, oligomerized N-terminal and full-length ANGPTL4 protein inhibits the activity of blood lipoprotein lipase thus influencing lipid metabolism [3e9]. However, in endothelial cells the C-terminus of ANGPTL4 represents a master regulator of vascular permeability and angiogenesis, as reviewed by Guo et al [33]. The C-terminus of ANGPTL4 alone has been shown to be sufficient to suppress angiogenesis through inhibiting the Raf/MEK/ERK signaling pathway in endothelial cells [34].…”
Section: Discussionmentioning
confidence: 98%
“…In the bloodstream, oligomerized N-terminal and full-length ANGPTL4 protein inhibits the activity of blood lipoprotein lipase thus influencing lipid metabolism [3e9]. However, in endothelial cells the C-terminus of ANGPTL4 represents a master regulator of vascular permeability and angiogenesis, as reviewed by Guo et al [33]. The C-terminus of ANGPTL4 alone has been shown to be sufficient to suppress angiogenesis through inhibiting the Raf/MEK/ERK signaling pathway in endothelial cells [34].…”
Section: Discussionmentioning
confidence: 98%
“…These genes included ANGPTL4, TCF7L2, and FOXP1. ANGPTL4 encodes a secreted protein which is involved in vascular permeability, angiogenesis, inflammatory responses, and glucose homeostasis in different tissues (18,19). TCF7L2 plays a key role in the Wnt signaling pathway and is involved in glucose homeostasis (20).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that ANGPTL4 participates in many inflammation responses, especially in lung inflammation and alveolar epithelial cell death, which could lead to ALI [24,25]. Whether it also plays an important role in H1N1-induced ALI remains unclear.…”
Section: Resultsmentioning
confidence: 99%